2018
DOI: 10.15835/nbha46110749
|View full text |Cite
|
Sign up to set email alerts
|

Solid Matrix Priming Treatment with O2 Enhanced Quality of Leek Seed Lots

Abstract: This study aims to determine the effect of solid matrix priming (SMP) treatment with an air composition of O 2 , N 2 , air, vacuum on four leek (Allium ampeloprasum L.) seed lots of various ages, in terms of enhancing germination, mean germination time, electrical conductivity of solute leakage and catalase activity. Untreated seeds were used as control. Solid matrix priming at a seed: vermiculite: water ratio of 2.5:1.25:3.75 (w/w/w) was applied at 20 °C for 24 hours in the dark. Solid matrix priming with O 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…It has been shown that the seeds subjected to SMP exhibit a higher germination rate, a shorter germination time, and lower electrical conductivity values [97]. Furthermore, SMP media with other components, such as an Na-based hydrogel (sodium polyacrylate) and O 2 , were found to yield more effective results, particularly pronounced in lower-quality seeds [98,99].…”
Section: Solid Matrix Priming (Smp)mentioning
confidence: 99%
“…It has been shown that the seeds subjected to SMP exhibit a higher germination rate, a shorter germination time, and lower electrical conductivity values [97]. Furthermore, SMP media with other components, such as an Na-based hydrogel (sodium polyacrylate) and O 2 , were found to yield more effective results, particularly pronounced in lower-quality seeds [98,99].…”
Section: Solid Matrix Priming (Smp)mentioning
confidence: 99%
“…It is also useful for increasing germination percentage and germination rates in many crop seeds. Rapid germination after SMP will mostly result in larger seedlings and well-developed transplants in the modules in a shorter period (Ozden et al, 2018). Many vegetable crops benefit greatly from solid matrix priming in terms of seed germination, seedling growth and protection from different biotic and abiotic stresses (Table 1 and Figure 1).…”
Section: Factors Effecting Germination Of Vegetable Cropsmentioning
confidence: 99%
“…Seeds of various species showed remarkable ultrastructural changes when treated with solid matrix priming (Ashraf & Foolad., 2005). SMP with O2 increase seed germination of aged leek seeds by initiating cell repair mechanisms (reduced solute leakage, increase antioxidant enzyme activity) as it improves seed respiration important for many metabolic activities (ATP) by transferring oxygen across seed coat to respiratory substrates (Ozden et al, 2018). In broccoli (Brassica oleracea) and cauliflower seedlings, SMP treatment increased peroxidase and catalase activity, as well as soluble sugar, proline, and soluble protein content (Wu et al, 2019).…”
Section: Effect Of Solid Matrix Priming On Biochemical Process In Ger...mentioning
confidence: 99%
See 1 more Smart Citation
“…They can be combined to strengthen the priming effect as reported by Madsen et al ( 2018 ), who tested a mixture containing calcium bentonite clay, diatomaceous earth, compost, worm castings, non-ionic alkyl terminated block copolymer surfactant, a plant growth regulator, a fungicide, a liquid fertilizer, and tap water. SMP carried out under enriched O 2 conditions turned out to be effective on low-quality leek ( Allium ampeloprasum L.) seeds (Ozden et al 2018 ). SMP improves the pre-germinative metabolism, field emergence, and establishment, especially in horticultural crops (Grzesik and Nowak 1998 ; Lutts et al 2016 ), cereals (Hacisalihoglu et al 2018 ), and native grasses (Madsen et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%